Nanoparticulate bioactive-glass-reinforced gellan-gum hydrogels for bone-tissue engineering - Gantar, Ana (2014)
his work presents bioactive-glass-reinforced gellan-gum spongy-like hydrogels (GG-BAG) as novel hydrophilic materials for use as the scaffolding in bone-tissue engineering. The reinforcement with bioactive-glass particles resulted in an improvement to the microstructure and to the mechanical properties of the material. These mechanical properties were found to be dependent on the composition and improved with the amount of bioactive glass; however, values necessary to accommodate biomechanical loading were not achieved in this study. Nevertheless, by incorporating the bioactive-glass particles, the composite material acquired the ability to form an apatite layer when soaked in simulated body fluid. Furthermore, human-adipose-derived stem cells were able to adhere and spread within the gellan-gum, spongy-like hydrogels reinforced with the bioactive glass, and remain viable, which is an important result when considering their use in bone-tissue engineering. Thus, hydrogels based on gellan gum and bioactive glass are promising biomaterials for use either alone or with cells, and with the potential for use in osteogenic differentiation.